The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1136/bmjopen-2021-059758
|View full text |Cite
|
Sign up to set email alerts
|

What factors are associated with utilisation of health services for the poor elderly? Evidence from a nationally representative longitudinal survey in China

Abstract: ObjectivesTo investigate the status and factors of healthcare service utilisation among the poor elderly in China.MethodsWe selected the poor elderly from the China Health and Retirement Longitudinal Study (CHARLS) from 2011 to 2015. The main outcome measures include utilisation indicators for the probability and costs of outpatient/inpatient services. Based on modified Andersen behaviour model, a two-part model is designed to analyse the factors of the health service utilisation of the poor elderly.ResultsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…A study done in China has reported a crucial role of the need factor in determining health service utilization among the elderly. This same study has reported financial difficulties as a barrier and education, having social security and poor health status as a facilitator to use health services [ 56 ]. Similar to our finding, a study done in India among the elderly has found health care utilization to increase significantly with multimorbidity [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study done in China has reported a crucial role of the need factor in determining health service utilization among the elderly. This same study has reported financial difficulties as a barrier and education, having social security and poor health status as a facilitator to use health services [ 56 ]. Similar to our finding, a study done in India among the elderly has found health care utilization to increase significantly with multimorbidity [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the difference in the relationship between air quality and health shocks, heterogeneity tests were conducted based on age, gender, and regional groups. According to the division of age from Hu et al ( 11 ) and Zeng et al ( 37 ), our samples were divided into 60–69 and 70+ years (we classified these two groups as “young-older” and “older,” respectively. The gender groups were divided into male samples and female samples.…”
Section: Resultsmentioning
confidence: 99%
“…Referring to Grossman's health needs theory and Zeng et al ( 37 ) regarding the delineation of control variables, and modified to fit the needs of the study, the individual control variables were divided into three categories: demographic characteristics, enabling variables, and social welfare ( 36 , 37 ). Demographic characteristics included sex, age, marital status, education level, and type of residence.…”
Section: Methodsmentioning
confidence: 99%
“…[48] In addition, based on the population from CHARLS, the low-literacy older adults were less likely to search for health services. [49] So, relevant strategies on internet education and health literacy promotion to encourage effective internet access should be underscored in developed and developing countries.…”
Section: Discussionmentioning
confidence: 99%